Analysis of the Fossilization Processes of Vicarya callosa japonica Shells Using Raman Micro-Mapping Combined with Principal Component Analysis and Partial Least Squares Regression - Tanaka, Yuki; Hashimoto, Kosuke; Ichiki, Toshiya; Sato, Hidetoshi; Ozaki, Yukihiro; Tsuboi, Motohiro (Applied spectroscopy, 2025)
Micro-Raman spectroscopic analysis of a fossil sample of was performed to investigate the chemical process of fossilization. The sample, originating from the Miocene Katsuta Group, Okayama prefecture, southwestern Japan, had a conical shell body with multiple protuberances on the outer layer. The interior of the shell was filled with a carbonate sediment. Raman mapping combined with principal component analysis (PCA) and partial least squares regression (PLSR) analysis were performed on the sample. Well-preserved, in vivo aragonite was found to be distributed on the shell and near the boundary between the internal carbonate precipitates and the shell. The internal precipitates were composed of pure calcite and black carbonates. The black-colored precipitates contained pyrite, suggesting that the carbonates were derived from the same biogenic tissue as the carbonate concretions and were the starting point for their crystallization. The rapid formation of the precipitates, also similar to that of carbonate concretions, and the suppression of the demineralization effect of the shell from pore water in the sediment may have contributed to the preservation of the aragonite. The reaction of the transition from aragonite to calcite in the shell progressed to some extent and crystallization was completed before the transition to calcite was complete.